Social mechanisms in crowdsourcing contests: a literature review. Issue 5 (4th April 2022) - Jain, Shilpi; Deodhar, Swanand J.
ABSTRACT: Crowdsourcing contests allow organisations to engage with an external workforce. Over the years, the phenomenon has attracted considerable research interest. In the present review, we synthesise the crowdsourcing contest literature by adopting the social mechanism lens. We begin by observing that stakeholders in crowdsourcing contests range from individuals (solvers) to large-scale organisations (seekers). Given that such vastly different entities interact during a crowdsourcing contest, it is expected that their behaviour, too, can have a varying range of predictors, such as individual and organisational factors. However, prior reviews on Crowdsourcing contests and crowdsourcing, in general, haven't explored the phenomenon's multi-layered nature. In addressing this gap, we synthesise 127 scholarly articles and identify underlying social mechanisms that explain key behavioural outcomes of seekers and solvers. Our review makes two specific contributions. First, we determine three distinct tensions that emerge from the key design decisions that might be at odds with the central principle of crowdsourcing contests: broadcast search for solutions from a long-tail of solvers. Second, we provide three recommendations for future research that, we believe, could provide a richer understanding of the seeker and solver behaviour.